2015
DOI: 10.5603/ait.2015.0055
|View full text |Cite
|
Sign up to set email alerts
|

Konflikty na oddziale anestezjologii i intensywnej terapii

Abstract: Conflicts in intensive care units (ICUs) are common and concern all professional groups, patients and their families. Both intra-and inter-team conflicts occur. The most common conflicts occur between nurses and physicians, followed by those within nursing teams and between ICU personnel and family members. The main causes of conflicts are considered to be unsatisfactory quality of the information provided, inappropriate ways of communication and improper approach towards treatment of patients. ICU conflicts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Indeed, simply recognizing conflict as a common, potentially beneficial aspect of relationships has positive implications for romantic partners (Gottman, 1999;Peleg-Koriat, Weimann-Saks, & Ben-Ari, 2018). In general, research has shown that when family members avoid conflict and view it as nonnormative and universally unhealthy, families suffer (Koerner & Fitzpatrick, 2006;Laursen & Hafen, 2009;Meeks, Hendrick, & Hendrick, 1998;Noller, Feeney, Bonnell, & Callan, 1994;Wujtewicz, Wujtewicz, & Owczuk, 2015).…”
Section: Implications For Practice With Familiesmentioning
confidence: 99%
“…Indeed, simply recognizing conflict as a common, potentially beneficial aspect of relationships has positive implications for romantic partners (Gottman, 1999;Peleg-Koriat, Weimann-Saks, & Ben-Ari, 2018). In general, research has shown that when family members avoid conflict and view it as nonnormative and universally unhealthy, families suffer (Koerner & Fitzpatrick, 2006;Laursen & Hafen, 2009;Meeks, Hendrick, & Hendrick, 1998;Noller, Feeney, Bonnell, & Callan, 1994;Wujtewicz, Wujtewicz, & Owczuk, 2015).…”
Section: Implications For Practice With Familiesmentioning
confidence: 99%
“…Conflicts are an inherent part of work within any organisation and may be defined as a situation in which opposing people, who support different solutions, participate [1,2]. They can arise between members of an interdisciplinary team (or between teams representing different departments), between patients and team members/family members, and patients' families and team members [1]. They may concern the decisions that families surrogates [3] have to make or stem from organisational problems or from the individual characteristics of team members [4].…”
Section: Introductionmentioning
confidence: 99%
“…Establishing professional and specialized relationship is one of the essential aspects of providing care in the CCU which requires a collaborative approach and should be respected by all the members of the unit (4). In this regard, Wujtewics et al (2015) stated that most of the conflicts in CCUs would usually be observed between nursing groups and physicians which are related to dissatisfaction with the received information, inappropriate communicational methods, and inappropriate treatment methods for the patients (5).…”
Section: Introductionmentioning
confidence: 99%